Association between Thyroid Function and Gall Stone Disease - Reza, Md Nahid; Faisal, M Fardil Hossain; Noor, Tahmina; Mahmud, Riaz; Miah, Monsur; Siddique, Ibrahim; Khan, Md Manir Hossain (KYAMC Journal, 2021)
Background: There was a long term perception that gall stone disease may have a hidden association to alteration of thyroid function. Objective: To find out the association between thyroid function status in gall stone disease. Materials and Methods: This case control study was conducted in department of Surgery, Bangabandhu Sheikh Mujib Medical University Hospital from July 2017 to June 2018. This study recruited 152 gall stone patients diagnosed with Ultrasonography (USG). The control group underwent USG to exclude any asymptomatic cholelithiasis. Fasting blood samples were taken from all participants for measurements of Fasting Blood Sugar (FBS), serum free thyroxine (FT4), serum thyroid stimulating hormone (TSH), total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). Results: The mean serum TSH levels among cases (3.56±4.6) was higher than controls (2.46±1.68) (p<0.05). Subclinical hypothyroidism was noted in 11.8% of cases and all were found female and 3.8% of controls, whereas hypothyroidism was detected in 3 (3.8%) controls and 22 (14.5%) cases. The mean total cholesterol levels in cases was much higher than in controls, and was significant (p<0.05). Conclusion: Hypothyroidism has a significant role on development of gall stone disease with increasing age especially in female. KYAMC Journal.2021;12(1): 36-40